An overall review: modified asphalt binder containing sasobit in warm-mix asphalt technology - Hainin, Mohd. Rosli; A. Aziz, Md. Maniruzzaman; Feizabadi, Shahab Moeini; Putra Jaya, Ramadhansyah; Abdul Hassan, Norhidayah; Mohd Jakarni, Fauzan (Penerbit UTM Press, 2015)
Increasing emission of greenhouse gases is an environmental issue, and it is a great concern to curb this problem from further harm to the environment. Warm-mix asphalt (WMA) is one of efforts to curb a reduction in the temperature at which asphalt mixes are produced. WMA can reduce the temperature to 100°C and even lower without compromising the performance of asphalt binder. WMA has various benefits such as, reduction of asphalt binder temperature, reduction in energy consumption and less air pollution. It reduces short-term aging, compacting effort and decreases temperature drop during transportation. Sasobit is one of the organic additives of warm mix asphalt. It is used as a binder modifier to produce rut resistant mixtures. It provides the option of reducing fume emissions, saving energy and reducing production cycles. Therefore, sasobit is the preferred additive for warm-mix asphalt (WMA). In addition, Complex shear modulus will be determined to find the rutting factor and fatigue factor for the asphalt binder (G*/Sinδ and G*Sinδ respectively). The overall purposes of this study are to determine the importance of using WMA as a green pavement and introducing sasobit for modifying virgin asphalt binder.